Empirical Evidence of Environmental Degradation Using Geospatial Technology in Tasik Temenggor, Royal Belum Perak, Malaysia - Salleh, Siti Aekbal; Kamaruzzaman, Kamilia; Pardi, Faezah; Abdullah, Muhammad Fuad; Foronda, Vladimir; Khushairi, Zulfadhlan Ahmad; Abu Hassan, Muhamad Soleh; Dom, Nazri Che (Geoplanning: Journal of Geomatics and Planning, 2025)
Freshwater ecosystems are vital ecosystems for life, but in reality, they face severe pressure from anthropogenic activities, climate change, and land use changes. These conditions cause the environmental degradation process to accelerate, as is the case in Lake Temenggor, Malaysia. This study examines environmental degradation in Tasik Temenggor, Malaysia, using geospatial techniques to analyze land surface temperature (LST), normalized difference vegetation index (NDVI), land use and land cover (LULC), water quality, and air temperature. The aim of this study is to identify factors associated with environmental degradation, specifically focusing on climate and meteorological parameters and analyzing their temporal changes through spatio-temporal analysis. Data used were obtained from Landsat 8 OLI/TIRS and field observations, processed using ArcGIS Pro with Principal Component Analysis (PCA) and Weighted Overlay Analysis (WOA). The results show increasing degradation in agricultural and development areas, while forest zones remain relatively stable. Consistent LST classification is applied across all years to ensure valid temporal comparisons. The integration of PCA and WOA demonstrates a robust methodological framework that supports effective environmental monitoring. These findings highlight the practical utility of geospatial techniques in conservation planning and suggest targeted interventions for high-risk areas. In conclusion, this study demonstrates the application of geospatial technology in monitoring and assessing environmental degradation in Tasik Temenggor.